The impact of biotechnology in Latin America social engagement - Bota Arqué, Alexandre (Acta Bioethica, 2003)
The unceasing advance of techno science, specifically biotechnology, has open a world full of new possibilities, not without risks. The article's purpose is to analyze the ecological and social conflicts that the introduction of biotechnology has generated in Latin America and to elucidate which are the relevant actors and fields where biotechnological development would not be transformed into a technocracy, but rather a place for public engagement, where biotechnology could be a possibility "appropriated" by society. To carry out this task it is necessary to identify which is the real situation, the risks, the institutional discourses and the fields where the different actors could interact, so that bioethics would operate not only as a mediator, but also hermeneutically. This reflection would not situate Bioethics only in an academic field, but it should create or look for mechanisms for the generation of bioethical praxis.